SMEs Portfolio of e-Recruitment: Malaysian Perspective - Poorangi, M.M.; Wong, E.S.K.; Negin, R. (IACSIT Press, 2011)
The purpose of this study is the analysis of the possibilities and difficulties of e-recruitment practices for SMEs in Malaysia, elaborating their effectiveness, and explaining some practical and managerial implications concerning these actions. Statistical analyses and empirical findings expressed here show that the attitudes and opinions of SME executives towards e-recruitment are considered a sub-function of an integrated e-HRM and can be seen as a valued technological improvement in the main critical activities of human resource management. However, findings show that the ability to communicate and deal with a multilingual organizational and working environment is the most important operational benefit of a web-based e-HRM and e-recruiting system. This technology is seen as a pathway to improving external and internal interactions and communication between job seekers, firms, employees, and other stakeholders, as well as to build data bases to store and recall data. These are the main strategic advantages of a recruitment system for SMEs in Malaysia. The findings of this study also show that e-recruitment in Malaysia is still in-progress work and even the big recruiting firms have not fully implemented this technology.